Identification of causal intensive margin effects by difference-in-difference methods - Markus Hersche; Elias Moor (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
This paper discusses identification of causal intensive margin effects. The causal intensive margin effect is defined as the treatment effect on the outcome of individuals with a positive outcome irrespective of whether they are treated or not (always-takers or participants). A potential selection problem arises when conditioning on positive outcomes, even if treatment is randomly assigned. We propose to use difference-in-difference methods - conditional on positive outcomes - to estimate causal intensive margin effects. We derive sufficient conditions under which the difference-in-difference methods identify the causal intensive margin effect in a setting with random treatment.
Keywords: C21; C24; C18; 330; Intensive margin effect; difference-in-difference; corner solution models; potential outcomes; policy evaluation